Respostas

2014-05-03T14:21:02-03:00
Δ = b² - 4.a.c
x =  \frac{-b +-  \sqrt{delta} }{2.a}


1)
2 x^{2} - 10x = 0
a = 2  b = -10  c = 0
Δ = (-10)² - 4·2·0
Δ = 100
x =  \frac{-(-10)+-  \sqrt{100} }{2.2} \\  \\ x =  \frac{10 +- 10}{4}  \\ \\   x_{1} =  \frac{10 + 10}{4}  =  \frac{20}{4} = 5

2)
 x^{2}  - 25x = 0
a = 1  b = -25  c = 0
Δ = (-25)² - 4·1·0
Δ = 625
x = -(-25)+-  \sqrt{625} \\ \\   x_{1} =  \frac{25 + 25}{2} =  \frac{50}{2} = 25

3)
4 x^{2} + 10x = 0
a = 4  b = 10  c = 0
Δ = 10² - 4·4·0
Δ = 100
x =  \frac{-10+- \sqrt{100} }{2.4}  \\  \\  x_{1} =   \frac{-10-10}{8} =  \frac{-20}{8} = -2,5